PENGARUH AIR LIMBAH CUCIAN BERAS TERHADAP BIOMASSA, PROTEIN, DAN PIGMEN KAROTENOID Arthrospira platensis - Anisa Millah Taqiyyah; Yenny Risjani; Asep Awaludin Prihanto; Gilang Drajat Maulana; Karimah Karimah (Jurnal Penelitian Pendidikan IPA, 2023)
Arthrospira platensis culture requires macro and micronutrients. The nutrients needed by Arthrospira platensis according to Agustina and Herman (2021) are macronutrients consisting of nitrogen (N), phosphorus (P), potassium (K), sulfur (S), iron (Fe), magnesium (Mg), silicon (Si), and calcium (Ca). Micronutrients consist of zinc (Zn), cobalt (Co), molybdenum (Mo), boron (B), and copper (Cu). Rice-washing wastewater contains macro and micronutrients needed for the growth of Arthrospira platensis. Almost all of the nutrients needed by Arthrospira platensis are found in the wastewater, except for Co. Previous studies have shown that rice-washing wastewater can be used for Arthrospira platensis culture, but the growth rate is still higher than Walne fertilizer 0.5 ml/L. Zarrouk fertilizer as a standard growth medium for Arthrospira platensis shows that this fertilizer has better growth results than Urea and NPK fertilizers. This research was conducted to determine the effect of rice-washing wastewater as a nutrient source for culture media or a combination of Zarrouk fertilizer and rice-washing wastewater so that it can be used to increase the biomass and carotenoid pigments of Arthrospira platensis. This research used a Factorial Completely Randomized Design (CRD) with 12 treatments and 3 replications. Arthrospira platensis quality test was carried out by testing dry biomass and carotenoid content. The ANOVA test results showed that this study's treatment had a significant effect on the carotenoid content and biomass of Arthrospira platensis. The treatment with the highest effect of biomass and carotenoids was obtained in the treatment of 1.5 ml/L of rice-washing wastewater